THz Thin Film Varactor Based on Integrated Ferroelectric HfZrO2 - Sukhrob Abdulazhanov, Quang Huy Le, Dang Khoa Huynh, Defu Wang, David Lehninger, Thomas Kämpfe, Gerald Gerlach (ACS Applied Electronic Materials, 2022)
In this paper, we present a broadband microwave characterization of ferroelectric hafnium zirconium oxide (Hf0.5Zr0.5O2) metal–ferroelectric–metal (MFM) thin film varactor from 1 kHz up to 0.11 THz. The varactor is integrated into the back-end-of-line (BEoL) of 180 nm CMOS technology as a shunting capacitor for the coplanar waveguide (CPW) transmission line. At low frequencies, the varactor shows a slight imprint behavior, with a maximum tunability of 15% after the wake-up. In the radio- and mmWave frequency range, the varactor’s maximum tunability decreases slightly from 13% at 30 MHz to 10% at 110 GHz. Ferroelectric varactors were known for their frequency-independent, linear tunability as well as low loss. However, this potential was never fully realized due to limitations in integration. Here, we show that ferroelectric HfO2 thin films with good back-end-of-line compatibility support very large scale integration. This opens up a broad range of possible applications in the mmWave and THz frequency range such as 6G communications, imaging radar, or THz imaging.